SMART CHARACTER SEBAGAI UPAYA MENUMBUHKAN JIWA KEPEMIMPINAN SISWA DI SMAN 1 JIWAN - Nugroho, Danang Dwi; Wahyono, Gatot Dwi; Yuliani, Lina; Wulandari, Esti; Agustina, Windarti (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Crisis of leadership is a serious problem that is faced by Indonesia today including by students. The Indonesianâs students have no ability to lead on themselves, the first step in rising leadership qualities. There are a lot of students, who are engaged in a gang fight, have low empathy and low respectful to others. âSmart Characterâ is a program which is concern about leadership and is applied as an effort to solve crisis of leadership by rising leadership qualities toward students. Methods that are used in applying âSmart Characterâ are: observation, consultation, socialization, weekly intensive character building, evaluation, and continuing the program. The output of the program is the rising of studentsâ leadership qualities.